Prevalence of smoking and high blood pressure, two major risk factors for non-communicable diseases: the SuRF NCD (surveillance of risk factors of non-communicable disease) report 2012 - Ahmad Jamalizadeh; Zahra Kamiab; Ali Esmaeili Nadimi; Mohsen Nejadghaderi; Ala Saeidi; Amirhossein Porkarami (Journal of Cardiovascular and Thoracic Research, 2016)
Introduction: In recent years non-communicable diseases (NCDs) risk factors such as tobacco consumption and high blood pressure (BP) have been increased. This study aimed to determine the frequency of risk factors of the main NCDs among inhabitants of Rafsanjan city. Methods: Our study is a part of NCD surveillance in Iran (SuRF NCD). A total of 640 people enrolled and divided in four age groups in urban and rural areas in Rafsanjan (a city in Kerman province). Data were collected using the standardized stepwise protocol for NCD risk factor surveillance of the World Health Organization (WHO). This study focused on hypertension (HTN) and smoking. Results: A total of 640 people (46.9% male and 53.1% female) participated in this cross-sectional study. The prevalence of HTN was 198 per 1000 population. 4.8% of those were below the age of 44, and 15% between 45 and 70 years old. Mean systolic BP was 127 ± 15.6 in male and 118 ± 19.65 in female and the statistical difference was significant (t = 5.55, P < 0.001). 79 (14.1%) of hypertensive live in urban and 32 (5.7%) live in rural areas (χ2 = 8.004, P = 0.005). The prevalence of current smokers was 112 per 1000 population; among them 56 (88.9%) were daily smokers. The mean age for starting smoking was 21.11 ± 7.16 years. Conclusion: Modifying risk factors such as HTN and smoking behavior through primary and secondary prevention programs by enhancing awareness and knowledge of lay people, improvement screening and treatment interventions, particularly for the youth is highly recommended.